New Frontiers in IVF: mtDNA and autologous germline mitochondrial energy transfer - Mauro Cozzolino; Diego Marin; Giovanni Sisti (BMC, 2019)
Abstract Many infertility specialists support the existence of a relationship between the levels of mitochondrial DNA and the quality of the blastocysts. Despite the extensive use of pre-implantation genetic testing for aneuploidy, a significant percentage of euploid embryos do not implant even though the endometrium is normal. Mitochondrial DNA may be used as a new test in evaluating embryonic vitality. Ovarian aging leads to a decrease in the quantity and quality of oocytes and aged oocytes have a reduced number of mitochondria. Mitochondria are the energy factories of the cells and their lacked could leads to lower fertilization rates and poor embryonic development. Various strategies have been tested to increase the mitochondria quantity and thus improve the quality of oocytes used in in vitro fertilization. Results of ovarian rejuvenation techniques such as autologous mitochondrial transplantation have been controversial. In this review, we describe the state of the art concerning the use of mitochondrial DNA and autologous mitochondrial transplantation as new possibilities to increase success in vitro fertilization.